The interplay of epigenetic therapy and immunity in locally recurrent or metastatic estrogen receptor-positive breast cancer: Correlative analysis of ENCORE 301, a randomized, placebo-controlled phase II trial of exemestane with or without entinostat. (1st November 2016) - Tomita, Yusuke; Lee, Min-Jung; Lee, Sunmin; Tomita, Saori; Chumsri, Saranya; Cruickshank, Scott; Ordentlich, Peter; Trepel, Jane B.
ABSTRACT: Entinostat, a class I-selective histone deacetylase inhibitor, has shown promising activity in ENCORE 301, a randomized, placebo-controlled, phase II trial of exemestane with or without entinostat in women with locally recurrent or metastatic estrogen receptor-positive breast cancer progressing on a nonsteroidal aromatase inhibitor. ENCORE 301 showed an 8.3-mo improvement in median overall survival among patients who received entinostat. We investigated the impact of entinostat on immune subsets with CD40, HLA-DR, and immune checkpoint receptor expression analyses in 34 patient blood samples from ENCORE 301. We found that entinostat significantly decreased granulocytic and monocytic MDSCs at cycle 1 day 15. MDSC CD40 was significantly downregulated by entinostat. A significant increase in HLA-DR expression on CD14 + monocytes by entinostat was observed. Entinostat did not impact T-cell subsets or T-cell immune checkpoint receptor expression. Our findings suggest that a significant interplay between this epigenetic regimen and host immune homeostatic mechanisms may impact therapeutic outcome.